Nutrient-rich food index 9.3 score and food choice values among female online food delivery users during COVID-19 pandemic - Nadya Suci Palupi; Dian Novita Chandra; Judhiastuty Februhartanty; Helda Khusun; Nisrina Hanisa; Dian Kusuma Dewi (World Nutrition Journal, 2024)
Background: The COVID-19 pandemic has transformed eating habits, leading to an increased reliance on online food delivery. It's crucial to comprehend the diet quality and food choices among female users during this period. Objective: This study aims to explore the association between diet quality score and the food choice motives among female online food delivery users during the COVID-19 pandemic Methods: This online cross-sectional study involved surveying 405 female users recruited through consecutive sampling. The Food Choice Values Questionnaire (FCVQ) was utilized to understand their food choices, while nutrient intake and diet quality were assessed using the Nutrient-Rich Food 9.3 Index Score (NRF 9.3). Subsequently, the collected data underwent both univariate and multivariate analyses. Potential biases might arise due to time constraints during the pandemic and reliance on self-reported online data. Moreover, the method used to measure nutrient intake might not be ideal for this demographic, lacking tailored tests. Nonetheless, it’s important to highlight that the survey underwent prior validation among Indonesian adults, affirming its broad applicability. Results: Female users showed low average NRF 9.3 scores (241.67), indicating poor diet quality. Their prioritized food choice motives were also low. Significant associations surfaced between NRF 9.3 scores and food choice motives—tradition (p<0.01, r: 0.229), comfort (p<0.01, r: 0.223), organic (p<0.01, r: 0.231), safety (p<0.001, r: 0.162), weight control/health (p<0.01, r: 0.171), and income (p<0.05). Conclusion: The NRF 9.3 score is likely to increase when there are higher scores for tradition, comfort, and organic factors, and when income exceeds the minimum regional wage.